MSME Product Quality Assistance through Halal Product Assurance Certification in Gondang Kulon Nganjuk Village - Hapsari Wiji Utami; Asiatus Sholeha; Muhammad Hamdan Luthfi; Muhammad Muzakky Adirangga; Novi Dwi Rachma Dani; Nur Aini Octavia; Yurinda Mutiarasari (Business Finence Analyst Co.,, 2024)
The purpose of this KKN activity is to provide training on the promotion and management of halal certification for MSMEs in GondangKulon village, Nganjuk Regency. The purpose of this analysis is to provide an understanding of the importance of registering a business and the benefits of halal certificates for its business products. This KKN activity consists of 2 types of implementation of halal certification assistance for business actors as well as submission of halal certification documents to SIHALAL UINSA and socialization of product promotion through marketing with E-Commerce in Gondangkulon Village, Nganjuk Regency. This type of research is qualitative and the method of this study uses ABCD, using 3 stages of data collection, namely interviews, observation and documentation. The result of this activity is the awareness of partner business units to implement a halal assurance system in their business and the registration of business units in the halal certification process to Si Halal.